The role of crop improvement in pest and disease management - Lorenzen, J.H.; Tenkouano, A.; Bandyopadhyay, Ranajit; Vroh Bi, Irie; Coyne, Danny L.; Tripathi, L. (International Society for Horticultural Science, 2009)
Pests and diseases have become major constraints to smallholder banana production in the highlands of East Africa. Biotic challenges to banana cultivation include fungi, bacteria, viruses, nematodes and insects. Host-plant resistance, developed either by conventional breeding or by application of biotechnology, is thought to be the most economic and sustainable means of managing pests and diseases. The deployment of host-plant resistance may be confounded by constraints on the process of introgression, such as complicated genetics, inadequate screening protocols and undesirable linkage drag, or by complexities in host plant-pest interactions, such as the occurrence of different strains and R gene specificity. Specific examples derived from both potato and banana pathosystems are described to illustrate progress in the deployment of host-plant resistance, possible problems related to pathogen diversity and R gene specificity, and methodology involved in developing resistant lines. Proactive management and monitoring are required to minimise the effects of changes to the pathosystem because of pathogen evolution or the introduction of exotic strains.